Developing a set of patient‐centered outcomes for routine use in endometriosis: An international Delphi study - Alba Nicolas‐Boluda; Enora Le Roux; Arounie Tavenet; Jerome Bouaziz; Paolo Vercellini; Pamela Stratton; Arnaud Fauconnier (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction There is large variation in individual patient care for endometriosis. A uniform approach to measure outcomes could be incorporated into routine clinical practice to personalize and monitor treatments and potentially improve the quality of care. The aim of this study is to identify a group of patient‐centered outcomes for use in routine endometriosis care which are relevant to all patient profiles. Material and Methods By means of a modified two‐round Delphi study with international representation including healthcare professionals, researchers and patient representatives (51 participants, 16 countries) we developed a set of patient‐centered measurements. The participants evaluated 47 Patient Reported Outcome Measures (PROMs) and 30 Clinician Reported Outcome Measures (CROMs) regarding their feasibility and relevance for their use in routine endometriosis care. After the two rounds of quotation, meetings of the experts were convened to participate in a final discussion to finalize the consensus of the final set of included measures. Results The final set of patient‐centered outcomes includes six PROMs (measuring symptomatic impact, pain, work productivity and quality of life) and 10 CROMs (measuring clinical, imaging and surgical indicators). A supplementary list of outcomes was added to include important dimensions that were considered essential by the expert panel but are not relevant to all patients. In addition the need for development of specific tools (PROMs) measuring the psychological impact and the impact in sexual activity of endometriosis was highlighted. Conclusions We have developed a set of patient‐centered outcomes measures in endometriosis care. The selected outcomes comprise the common features for all patients suffering from endometriosis. adapted for use in routine practice. The list of outcomes has been adapted for use in routine practice from which clinicians can chose, depending on their needs.